(untitled) (Biological Sciences - PJSIR, 2001)
Co (II), Ag (I) and Hg (II) or Co (II), Ni (II), Fe (II), Cu (II) and Hg (II) are simultaneously extracted as metal chelates compounds of 2-thiophenaJdehyde-4-pheny1-3-thiosemicarbazone (TAPT) in chloroform. The complexes were separated from microsorb C-18, 5 urn column when eluted with methanolJacetonitrile/water/aqueous sodium acetate 1m mol or methanolJacetonitrile/water/sodium acetate (Immol) tetrabutyl ammonium bromide (Immol) with a flow rate of Iml:’ and detection UV at 254 nm. Linear calibrations were made with 10-50 ug ml’ and detection limit was 0.4 ug ml’, corresponding to 2 ng/injection in Co and Hg. The method was used for the determination of mercury in surface water fishes. It was found within 0.125 to 1.18 ug g-! offish muscles with coefficient of variation (C.V) 3.4-5.8%.